Repair of Bone Erosion in Rheumatoid Arthritis by Denosumab: A High‐Resolution Peripheral Quantitative Computed Tomography Study. Issue 8 (10th July 2017) - Yue, Jiang; Griffith, James F.; Xiao, Fan; Shi, Lin; Wang, Defeng; Shen, Jiayun; Wong, Priscilla; Li, Edmund K.; Li, Martin; Li, Tena K.; Zhu, Tracy Y.; Hung, Vivian W.; et al.
Abstract : Objective: To compare the bone healing effects of denosumab and alendronate in female rheumatoid arthritis (RA) patients by high‐resolution peripheral quantitative computed tomography. Methods: This is a post hoc analysis of a randomized controlled trial. Forty patients were randomized in a 1:1 ratio to receive either subcutaneous denosumab (60 mg) once or oral alendronate (70 mg) weekly for 6 months. The size of individual bone erosions and the presence and extent of erosion‐associated sclerosis (marginal osteosclerosis) were measured in the second metacarpal head of the nondominant hand at baseline, 3 months, and 6 months. Results: Forty‐two erosions were identified at baseline. After 6 months, the width, depth, and volume of erosion significantly decreased in the denosumab group (−0.23 mm, −0.16 mm, −0.91 mm 3, respectively; all P  < 0.01), whereas these parameters significantly increased in the alendronate group (0.19 mm, 0.32 mm, and 1.38 mm 3, respectively; all P  < 0.01; between‐group differences, P  < 0.01 for all). Quantitative analysis showed that the bone mineral density of the erosion margin significantly increased only after treatment by denosumab (19.75 mg/cm 3 ; P  < 0.05 for denosumab, and −5.44 mg/cm 3 ; P  = 0.51 for alendronate; P  < 0.05 for between‐group differences). Conclusion: Inhibition of receptor activator of NF‐κB ligand by denosumab can induce partial repair of erosions in patients with RA, while erosions continued to progress in patients treated with alendronate. Combining denosumab with disease‐modifying antirheumatic drugs may be considered for RA patients with progressive bone erosions.